A leaning amine–ketone dyad with a nonconjugated linker: solvatofluorochromism and dual fluorescence associated with intramolecular charge transfer. Issue 9 (31st July 2018) - Kuramoto, Yutaro; Nakagiri, Takanobu; Matsui, Yasunori; Ohta, Eisuke; Ogaki, Takuya; Ikeda, Hiroshi
Abstract : A amine–ketone dyad with a nonconjugated linker displays solvatofluorochromism and dual fluorescence due to intramolecular charge transfer in the excited state accompanied by a change of the molecular geometry like leaning. Abstract : Dyad4, comprising a triphenylamine (TPA) electron donor and 1, 4-pentadien-3-one (pentadienone) electron acceptor tethered by a nonconjugated linker, displays solvatofluorochromism (SFC) and dual fluorescence associated with intramolecular charge transfer (ICT) in the excited state. While the fluorescence arises from a locally excited state of4 (LE-4* ) in saturated hydrocarbon solvents, the fluorescence from the ICT state of4 (ICT-4* ) occurs in aprotic solvents. ICT-4* has a much greater dipole moment than its corresponding ground state. The results of theoretical calculations suggest that the conversion of LE-4* to ICT-4* involves a unique structural change like a leaning of the pentadienone moiety. Two factors are responsible for the significant SFC displayed by4, the first being the high electron-donating and -accepting abilities of the respective locally excited TPA and pentadienone moieties in LE-4* and the other being a rigid ethano bridge that links the two moieties in ICT-4* . The former property facilitates photoinduced electron-transfer (PET) and the latter prevents full single electron transfer (SET) by prohibiting direct π-conjugation and the spatial approach of the two dyad components. Consequently, these electronic and geometrical features lead to SFC arising from a large dipole moment change caused by ICT and partial intramolecular SET.